2015
DOI: 10.1134/s0036024415030279
|View full text |Cite
|
Sign up to set email alerts
|

Density, partial, and excess volumes of solutions of methacrylic acid in organic solvents at 293 K

Abstract: The densities of solutions of methacrylic acid in acetonitrile, benzene, hexane, 1,2 dichloro ethane, and acetic acid at a temperature of 293 K and atmospheric pressure are determined by means of pyc nometry. The values of the excess molar volume for the studied systems and those of the partial molar volumes of the components are calculated. It is found that the excess molar volume of binary systems of methacrylic acid with benzene, hexane, 1,2 dichloroethane, and acetic acid is positive over the range of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This work is a continuation of a series of our studies related to the determination of thermodynamic parameters of individual organic compounds and their solutions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 96%
“…This work is a continuation of a series of our studies related to the determination of thermodynamic parameters of individual organic compounds and their solutions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 96%
“…It is widely used to produce methyl methacrylate (MMA), an important basic organic chemical material, because it has two functional groups, carbon double bond and a carboxyl group, and can conduct polymerization and esterification reactions. In addition, MAA can also be used as raw materials for synthetic rubber, thermosetting paint, synthetic rubber, fabric treatment agent, etc. With the continuous attention paid to biomass fuel, a large number of experiments have shown that the chemicals and intermediates produced by biomass fuel can effectively replace some coal-based materials, which not only compound the concept of environment friendly, but also can develop downstream industries for industrialization and commercialization. One of the fields is to synthesize important vinyl polymers in the industry from biomass raw materials, such as methacrylic acid (MAA) and methyl methacrylate (MMA) …”
Section: Introductionmentioning
confidence: 99%